IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM UPAYA MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA SEKOLAH DASAR - Dewi, Nastitisari; Sumantri, Syarif; Gumelar, Gumgum (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to examine the implementation of the Problem-Based Learning (PBL) model in improving the creative thinking skills of elementary school students. PBL is considered one of the innovative learning models that emphasizes solving real-world problems, collaboration, and the development of higher-order thinking skills. This research employed a Classroom Action Research (CAR) method with a qualitative approach, conducted on 30 fifth-grade students at SDN Benteng 3, Sukabumi City. Data were collected through observation, interviews, documentation, and creative thinking skill tests, and were analyzed using qualitative descriptive techniques. The results revealed a significant improvement in students’ creative thinking skills after the implementation of PBL. The average score increased from 34.55 (pretest) to 59.76 in the first cycle (N-Gain 39.27%, medium category) and reached 71.21 in the second cycle (N-Gain 56.38%, medium category). The most prominent improvement was observed in the indicators of flexibility and originality, while fluency, elaboration, and evaluation also showed positive progress, albeit more moderately. These findings indicate that PBL not only makes learning more interactive, collaborative, and contextual but also provides opportunities for students to generate diverse ideas, develop innovative solutions, and make critical judgments about problems. Therefore, this study confirms that PBL is effective and relevant to be continuously implemented in elementary schools to foster creative thinking skills, which are among the essential competencies required in the 21st century.